2002
DOI: 10.1002/etc.5620211224
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of chelator‐facilitated metal uptake by a halophyte and a glycophyte

Abstract: Phytoextraction is the use of plants to remove contaminants, in particular metals, from soil via root uptake and translocation to the shoots. Efficient phytoextraction requires high-biomass plants with efficient translocating properties. Halophytes characteristically accumulate large quantities of salts in above ground tissue material and can have high biomass production. It has been speculated that salt-tolerant plants may also be heavy metal tolerant and, further, may be able to accumulate metals. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Humic acid stimulated the transport of Cu, as well as that of Pb and Fe, from the roots to the shoots, whereas it decreased the transport of Mn ( p < 0.05). The increased transport of Cu and Pb to the shoots in the presence of a ligand has been demonstrated before, when EDTA was used as a ligand in a soil experiment [40]. In the present study, the increased transport (expressed as the ratio of shoot and root content) of Cu, Pb, and Fe was caused by a decreased metal content in the roots rather than by an increased metal content in the shoots, whereas the decreased transport of Mn was caused by an increased content in the roots rather than by a decreased content in the shoots.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Humic acid stimulated the transport of Cu, as well as that of Pb and Fe, from the roots to the shoots, whereas it decreased the transport of Mn ( p < 0.05). The increased transport of Cu and Pb to the shoots in the presence of a ligand has been demonstrated before, when EDTA was used as a ligand in a soil experiment [40]. In the present study, the increased transport (expressed as the ratio of shoot and root content) of Cu, Pb, and Fe was caused by a decreased metal content in the roots rather than by an increased metal content in the shoots, whereas the decreased transport of Mn was caused by an increased content in the roots rather than by a decreased content in the shoots.…”
Section: Resultsmentioning
confidence: 73%
“…Zinc and Ni were transported relatively easily through the plant, whereas Cd, Cu, Pb, Fe, and Mn accumulated mainly in the root system. In an earlier experiment of metal uptake by plants in soil, it also was found that Cu and Pb accumulated in the root system but that Zn was transported mainly to the shoots [40].…”
Section: Resultsmentioning
confidence: 99%
“…The EDTA is known to be a persistent nonassimilable ligand (although recent evidence observed with higher plants argues that intact metal EDTA complexes can be assimilated [38–40]), while citrate can be assimilated and in some occasions was shown to increase metal uptake and toxicity beyond the prediction of the FIAM [17,18]. Uptake of uranium gradually decreased with the addition of EDTA and citrate, as expected from the complexation of the free UO 2+ 2 ion (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…In particular, Atriplex species have a high tolerance to metal stress (Lutts et al ., ; Sai Kachout et al ., ). They can be irrigated with saline water and can also tolerate drought, freezing and heat (Thomas et al ., ; Jordan et al ., ; Lutts et al ., ).…”
Section: Introductionmentioning
confidence: 97%